A Single-Stage Quadrature LMVs - Nam-Jin Oh (Institute of Advanced Engineering and Science, 2018)
This paper proposes three kinds of single stage RF front-end, called quadrature LMVs (QLMVs), by merging LNA, single-balanced mixer, and quadrature voltage-controlled oscillator (VCO) exploiting a series LC (SLC) network. The low intermediate frequency (IF) or baseband signal near dc can be directly sensed at the drain nodes of the VCO switching transistors by adding a simple resistor-capacitor (RC) low-pass filter (LPF). Using a 65 nm CMOS technology, the proposed QLMVs are designed. Oscillating at around 2.4 GHz band, the proposed QLMVs achieve the phase noise below ‒107 dB/Hz at 1 MHz offset frequency. The simulated voltage conversion gain is larger than 30 dB. The double-side band (DSB) noise figure (NF) of the proposed QLMVs is below 10 dB. The QLMVs consume less than 0.51 mW dc power from a 1-V supply.